Quality of life in adults with congenital heart disease: what matters? - Kahl, Kai G.; Westhoff-Bleck, Mechthild (Journal of Thoracic Disease, 2016)
Advances in medical treatments for adults with congenital heart disease (ACHD) has resulted in reduced mortality, i.e., an increase in patients’ life expectancy. Consequentially, questions concerning quality of life (QoL) and its determinants paralleled this medical progress. The development of standardized and validated questionnaires facilitates the measurement of factors differentially influencing QoL.